Cyp26 enzymes function in endoderm to regulate pancreatic field size - Kinkel, Mary D; Sefton, Elizabeth M; Kikuchi, Yutaka; Mizoguchi, Takamasa; Ward, Andrea B; Prince, Victoria E (Proceedings of the National Academy of Sciences - PNAS, 2009)
The control of organ size and position relies, at least in part, upon appropriate regulation of the signals that specify organ progenitor fields. Pancreatic cell fates are specified by retinoic acid (RA), and proper size and localization of the pancreatic field are dependent on tight control of RA signaling. Here we show that the RA-degrading Cyp26 enzymes play a critical role in defining the normal anterior limit of the pancreatic field. Disruption of Cyp26 function causes a dramatic expansion of pancreatic cell types toward the anterior of the embryo. The cyp26a1 gene is expressed in the anterior trunk endoderm at developmental stages when RA is signaling to specify pancreas, and analysis of cyp26a1/giraffe (gir) mutant zebrafish embryos confirms that cyp26a1 plays the primary role in setting the anterior limit of the pancreas. Analysis of the gir mutants further reveals that cyp26b1 and cyp26c1 function redundantly to partially compensate for loss of Cyp26a1 function. We used cell transplantation to determine that Cyp26a1 functions directly in endoderm to modulate RA signaling and limit the pancreatic field. Taken together with our finding that endodermal expression of cyp26 genes is subject to positive regulation by RA, our data reveal a feedback loop within the endoderm. Such feedback can maintain consistent levels of RA signaling, despite environmental fluctuations in RA concentration, thus ensuring a consistent size and location of the pancreatic field.